Impact of Reduced Rainfall on Above Ground Dry Matter Production of Semi-natural Grassland in South Gloucestershire, UK: A Rainfall Manipulation Study - Ayling, S. M.; Thompson, Jill; Gray, A.; McEwen, L. J. (Frontiers in Environmental Science, 2021)
In the United Kingdom, agricultural grasslands cover 40% of the land area, make up 89% of the total agricultural area and are an important land use for ecosystem services and food security. Climate change predictions suggest that the United Kingdom will experience more frequent and severe periods of drought that may impact these grasslands. As part of the Drought Risk and You (DRY) project, a field experiment in which rain shelters reduced precipitation reaching the vegetation by approximately 50%, was set up in the South West of England. The experiment ran for 3 years, from October 2015 to October 2018. The study was carried out at two locations in the catchment of the Bristol River Frome. Both sites were species-rich semi-natural pastures that had received no inputs of fertilizer or herbicide for many years. Automatic weather stations recorded environmental conditions, especially rainfall, within the experimental area. The existing agricultural management regimes were approximated by cutting the vegetation in the plots, by hand, at the appropriate times of year. The effect of rainfall reduction on plant growth was assessed by biomass sampling. At both sites, the rainfall reduction treatment had only small effects on total above ground dry matter production (biomass). These effects were much smaller than the year-to-year variation in total biomass. Our results suggested that well-established permanent pastures in the South West of England were able to tolerate a 3-year period of reduced water supply. The observed year-to-year variation in biomass demonstrated how important the timing of dry weather is for biomass production, and this will be reflected in effects on yield and quality of hay.